PROSES ADOPSI INOVASI PROGRAM GERAKAN PENERAPAN PENGELOLAAN TANAMAN TERPADU (GP-PTT) KEDELAI - Naisah, Naila Hijrotin; Subekti, Sri; Widjayanthi, Lenny (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2016)
Soybean demand continues to increase, so the government strives to increase soybean production through the Soybean Integrated Crop Management Implementation Movement Program (Gerakan Penerapan Pengelolaan Tanaman Terpadu/GP-PTT Kedelai). This study aims to analyse the process of innovation adoption. Determination of research area is selected intentionally in Sukorejo Jember, particularly Rejeki farmers group. The study is a qualitative research with case study method. Determination of respondents was conducted using purposive sampling. Data was retrieved through depth interview, observation and unstructured documents. Data Analysis was performed using Miles and Huberman of data reduction model, data presentation, conclusion. Data validity was tested using source triangulation technique. Result showed that the adoption process included the following steps: (1) farmers knowledge was influenced by the characteristics of the decision making units regarding social and economic issues such as: a) the farmers who grow and apply the cultivation technology were old, b) the group members accepted technology due to the existence of government aid, communication behaviour related to the extension officers extension delivery; (2) the farmers attitude in claiming programs such as GP-PTT; (3) the decision declaring farmers to adopt the cultivation innovation; (4)the farmers failed to implement the recommended cultivation technology correctly; (5) the farmers confirmations that some resumed the technology and some didnt.